Microbes : the good, the bad, and the ugly - Randolph, Joanne (Amazing human body (Enslow Publishing), 2018)
Journeys inside the human body to explore the types of microbes found there, and discusses their role in one's health. Also discusses the discovery of microbes. Includes color photographs, a glossary, and further resources.